Low presence of papillomavirus and its lack of correlation with clinicopathological factors in breast cancer: a case control study - Manoochehr Makvandi; Mohammad Rashno; Ebrahim Faghihloo; Shahram Bagheri; Saeed Hesam; Habibollah Mirzaei; Ali Ramezani (Iranian Journal of Microbiology, 2023)
Background and Objectives: Breast cancer is currently the most commonly diagnosed neoplasm in women worldwide. There is evidence that human papillomavirus (HPV) infection may play a key role in breast cancer aggressiveness, but results are conflicting across studies. The aim of this study was to investigate the presence of the HPV viral genome in benign and malignant breast tissue samples and its clinicopathological characteristics of cancer. Materials and Methods: In this case-control study, 100 formalin-fixed paraffin-embedded (FFPE) of breast cancer and 100 blocks of non-cancerous breast tissue were selected as a control group from the pathology department of Imam Khomeini Hospital in Ahvaz from 2020-2022. The presence of HPV was detected using nested PCR including MY09/11 primers and sequencing were performed for virus genotyping. Results: The present study enrolled 100 subjects each in two cancer and control groups with a mean age of 52.81±13.23 and 35.77±11.65, respectively. The risk of cancer in HPV-infected patients is almost 5 times higher than in HPV-negative individuals, it is not statistically significant (OR =4.99, 95% CI 0.35 to 72.15, p=0.238). The prevalence of HPV in the cancer and control groups was 7% and 1%, respectively and HPVs detected in two groups were of the HPV 16 genotype. Although the chance of ER and PR expression, lymphvascular involvement, perineural invasion, and higher tumor grade was higher in HPV-positive subjects than in HPV-negative subjects, this was not statistically significant (OR>1, p>0.05). Conclusion: Based on studies reporting the existence of sequences of different high-risk HPV types (oncogenes) in breast cancer tissues, this study confirmed the hypothesis of a possible infectious cause in the development of breast cancer. So far, however, the results have been controversial and inconclusive. Further studies with large sample sizes are needed to demonstrate the link between HPV and breast cancer.